A Single-Institutional Experience with 36 Children Smaller Than 5 Kilograms Supported with the Berlin Heart Ventricular Assist Device (VAD) over 12 Years: Comparison of Patients with Biventricular versus Functionally Univentricular Circulation. Issue 2 (March 2023) - Bleiweis, Mark S; Philip, Joseph; Peek, Giles J; Stukov, Yuriy; Janelle, Gregory M; Pitkin, Andrew D; Sullivan, Kevin J; Nixon, Connie S; Sharaf, Omar M; Neal, Dan; Jacobs, Jeffrey P
Objectives: We reviewed outcomes in all 36 consecutive children <5 kg supported with the Berlin Heart pulsatile ventricular assist device (VAD) at the University of Florida, comparing those with univentricular circulation (n = 23) to those with biventricular circulation (n = 13). Methods: The primary outcome was mortality. Kaplan-Meier methods and log-rank tests were used to assess group differences in long-term survival after VAD insertion. T -tests using estimated survival proportions and standard errors were used to compare groups at specific time points. Results: Of all 82 patients ever supported with Berlin Heart at our institution, 49 (49/82 = 59.76%) weighed <10 kg and 36 (36/82 = 43.90%) weighed <5 kg. Of these 36 patients who weighed <5 kg, 26 (26/36 = 72.22%) were successfully bridged to transplantation. Of these 36 patients who weighed <5 kg, 13 (13/36 = 36.1%) had biventricular circulation and were supported with 12 biventricular assist devices (BiVADs) and 1 left ventricular assist device (LVAD) (Age [days]: median = 67, range = 17–212; Weight [kilograms]: median = 4.1, range = 3.1–4.9), while 23 (23/36 = 63.9%) had univentricular circulation and were supported with 23 single ventricle-ventricular assist devices (sVADs) (Age [days]: median = 25, range = 4–215; Weight [kilograms]: median = 3.4, range = 2.4–4.9). Of 13 biventricular patients who weighed <5 kg, 12 (12/23 = 92.3%) were successfully bridged to cardiac transplantation. Of 23 functionally univentricular patients who weighed <5 kg, 14 (14/23 = 60.87%) were successfully bridged to cardiac transplantation. For all 36 patients who weighed <5 kg: 1-year survival estimate after VAD insertion = 62.7% (95% confidence interval [CI] = 48.5%-81.2%) and 5-year survival estimate after VAD insertion = 58.5% (95% CI = 43.8%-78.3%). One-year survival after VAD insertion: 84.6% (95% CI = 67.1%-99.9%) in biventricular patients and 49.7% (95% CI = 32.3%-76.4%) in univentricular patients, P = 0.018. Three-year survival after VAD insertion: 84.6% (95% CI = 67.1%-99.9%) in biventricular patients and 41.4% (95% CI = 23.6%-72.5%) in univentricular patients, P = 0.005. Conclusion: Pulsatile VAD facilitates bridge to transplantation in neonates and infants weighing <5 kg; however, survival after VAD insertion in these small patients is less in those with univentricular circulation in comparison to those with biventricular circulation.